Internalisasi nilai-nilai wudlu dalam kacamata kedokteran maupun tasawuf sebagai respon living sunnah masa kini - Muhtadillah, Fadel Muhammad (Maliki Interdisciplinary Journal, 2024)
This study aims to explore the internalization of the values of wudhu from the perspectives of medicine and Sufism as a response to the concept of Living Sunnah in the present day and to examine the spiritual and health values of the practice of wudhu, as well as how these values can be internalized in daily life as part of Living Sunnah. The history of wudhu as one of the obligatory practices in Islam encompasses both spiritual and physical cleanliness aspects that have been practiced since the time of the Prophet Muhammad (صلى الله عليه وسلم). The urgency of wudhu lies in its ability to cleanse the soul and body, prepare individuals for worship, and maintain health. From a Sufism perspective, wudhu not only cleanses the body but also purifies the heart and mind, bringing one closer to Allah (سبحانه وتعالى). From a medical standpoint, wudhu has health benefits such as enhancing personal hygiene, preventing skin diseases, and supporting the immune system. The research method used is a qualitative approach with literature study and in-depth interview techniques. The literature study includes the analysis of classical and contemporary texts about wudhu in Islam, while in-depth interviews are conducted with Sufi and medical experts to obtain comprehensive perspectives. The results of this study are expected to provide a deeper understanding of the importance of wudhu in modern life and how this practice can harmoniously support physical and spiritual health.